Meta-analysis in metastatic uveal melanoma to determine progression free and overall survival benchmarks: an international rare cancers initiative (IRCI) ocular melanoma study. (31st May 2019) - Khoja, L; Atenafu, E G; Suciu, S; Leyvraz, S; Sato, T; Marshall, E; Keilholz, U; Zimmer, L; Patel, S P; Piperno-Neumann, S; Piulats, J; Kivelä, T T; et al.
Abstract: Background: Despite the completion of numerous phase II studies, a standard of care treatment has yet to be defined for metastatic uveal melanoma (mUM). To determine benchmarks of progression free survival (PFS) and overall survival (OS), we carried out a meta-analysis using individual patient level trial data. Methods: Individual patient variables and survival outcomes were requested from 29 trials published from 2000 to 2016. Univariable and multivariable analysis were carried out for prognostic factors. The variability between trial arms and between therapeutic agents on PFS and OS was investigated. Results: OS data were available for 912 patients. The median PFS was 3.3 months (95% CI 2.9–3.6) and 6-month PFS rate was 27% (95% CI 24–30). Univariable analysis showed male sex, elevated (i.e. > versus ≤ upper limit of normal) lactate dehydrogenase (LDH), elevated alkaline phosphatase (ALP) and diameter of the largest liver metastasis (≥3 cm versus <3 cm) to be substantially associated with shorter PFS. Multivariable analysis showed male sex, elevated LDH and elevated ALP were substantially associated with shorter PFS. The most substantial factors associated with 6-month PFS rate, on both univariable and multivariable analysis were elevated LDH and ALP. The median OS was 10.2 months (95% CI 9.5–11.0) and 1 year OS was 43% (95% CI 40–47). The most substantial prognostic factors for shorter OS by univariable and multivariable analysis were elevated LDH and elevated ALP. Patients treated with liver directed treatments had statistically significant longer PFS and OS. Conclusion: Benchmarks of 6-month PFS and 1-year OS rates were determined accounting for prognostic factors. These may be used to facilitate future trial design and stratification in mUM.